Biaya Audit Dalam Konvergensi Ifrs - Itan, Iskandar; Ervi, Ervi (Global Financial Accounting Journal, 2017)
This Study Aimed To Analyze The Effect Of Auditee Size, Audit complexity, client risk and Big4 vs non-big4 to audit fee for the company listed in Indonesia Stock Exchange (IDX) with observation period from 2009 to 2013. The statistical methods that used in this research was multiple regression method. Independent variables wereauditee size, audit complexity, client risk and Big4vs non-big4, while the dependent variable was audit fee.The data obtained were secondary data that sourced from the annual financial report for the companies in Indonesia Stock Exchange. This research used 208 sample of companies listed with purposive sampling. All samples have the following data such as total asset, total liabilities, total subsidiaries, and the company was audited by big4 or non-big4. The results indicated that auditee size, audit complexity, client risk and big4 vs non-big4 have a significant positive effect with audit fee. The effect of the four independent variables (auditee size, audit complexity, client risk, and big4 vs non-big4) with the dependent variable (audit fee) by 89,79%.